Yellow-billed Kite Milvus aegyptius nesting dynamics and breeding success across a human-modified landscape - Porter, Roger N; Howells, William W; Weiersbye, Ingrid B; Hoffman, Ben; Porter, Sean N (Ostrich, 2025)
Anthropogenic habitat transformation is one of the leading causes of biodiversity decline. Migratory birds, particularly many raptor species, are increasingly threatened by global environmental change. We investigated the nesting dynamics and potential determinants of breeding success in a population of the Yellow-billed Kite Milvus aegyptius across a human-modified landscape in an area of KwaZulu-Natal Province, South Africa. We monitored Yellow-billed Kite nests in a 17-km 2 study area every ∼3 days throughout the 2016-2017, 2017-2018 and 2018-2019 austral spring- summer during the breeding season. The average (±SD) nest density was 3.3 ± 0.4 nests per km 2 . Nearest-neighbour nest distance increased significantly with increasing distance to the nearest regular food source, a Nile crocodile Crocodylus niloticus farm. Cultivated and open woodland landcover were consistently avoided for nesting, while riparian landcover was preferred. Nest build day and intraspecific pressure were significantly negatively related to success in raising a free-flying juvenile, while the distance to the nearest crocodile farm and landcover type were not. Free-flying juveniles per nest ranged from 0 to 3, with an average (±SE) of 1.31 ± 0.02 juveniles per nest. The number of free-flying juveniles raised was significantly negatively related to intraspecific pressure but not to nest build day, distance to the crocodile farm or landcover type. The conservation implications of our findings are relevant to other breeding Yellow-billed Kite populations likely experiencing similar anthropogenic pressures. The availability of suitable nesting habitat, especially riparian areas characterised by dense vegetation and tall trees, is critical for maintaining the population in human-modified landscapes subjected to land transformation. Although surplus and consistent food did not influence breeding success, sufficient food resources may mitigate population decline in areas prone to land transformation by influencing an increase in nest density, until intraspecific pressure exceeds a threshold.